Healthcare systems barriers and strategies for pre-exposure prophylaxis utilization amongst young females in Gauteng province: Registered nurse’s perspectives - Doreen Onkarabile Mudau; Fhumulani Mavis Mulaudzi; Nombulelo Veronica Sepeng; Rafiat Anokwuru (PLoS ONE, 2025)
Background Healthcare system present several barriers impacting on Pre-Exposure Prophylaxis (PrEP) utilization amongst young females. To overcome these barriers, there are strategies that could be employed to improve PrEP performance. Within healthcare system, registered nurses play critical role on PrEP utilization, however their perceptions on barriers and strategies have not been explored and described in this setting. Therefore, this paper aimed at exploring, describing and contextualizing registered nurse’s perceptions on health systems barriers and strategies regarding PrEP utilization amongst young females. Methods Qualitative, explorative, descriptive and contextual method was used to explore and describing registered nurse’s perceptions on healthcare systems barriers and strategies regarding PrEP utilization. Purposively sampled participants for focus group discussions and data was analysed using reflexive thematic analysis. Results Barriers and strategies regarding PrEP utilization were reported as themes which emerged with eight sub-themes. Which included; healthcare system structure, healthcare providers, health promotion and medication barriers and strategies. Healthcare system structural barriers included limited PrEP access, healthcare workers related comprised training, competency and staffing while health promotion included poor awareness, inaccurate PrEP information, HIV-ART related stigma. Pill related barriers were side effects, contraindication and monitoring burden crucial to be addressed to enhance PrEP usage. Moreover, strategies such as increased access, PrEP integration to existing HIV, FP services, Department of Education and training of nurses on PrEP would assist to overcome these barriers. Proactively managing side-effects, increased awareness, using media platforms to disseminate information, quality counselling and three-monthly injectable PrEP for the success of desired utilization amongst young females. Conclusion Findings reported healthcare system structure, healthcare providers, health promotion and medication barriers and strategies affecting utilization of PrEP voiced by registered nurses within focus group discussions.